The Anti-colitis Effect of Schisandra chinensis Polysaccharide Is Associated With the Regulation of the Composition and Metabolism of Gut Microbiota - Su, Lianlin; Mao, Chunqin; Wang, Xiachang; Li, Lin; Tong, Huangjin; Mao, Jing; Ji, De; Lu, Tulin; Hao, Min; Huang, Ziyan; Fei, Chenghao; Zhang, Kewei; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: The pathogenesis of inflammatory bowel disease (IBD) is linked to an intricate association of environmental, microbial, and host-related factors. Polysaccharide affects host immunity by regulating the composition and metabolism of gut microbiota is the common mechanism of disease resistance. However, the efficacy and mechanism of Schisandra chinensis polysaccharide (SCP) in the treatment of inflammatory bowel disease have not been studied. Objective: To explore the effect and mechanism of SCP on dextran sodium sulfate (DSS) - induced ulcerative colitis (UC) in mice. Materials/Methods: In this study, we established a mouse model of UC, and used SCP for treatment intervention. The biochemical indexes related to inflammation were determined by ELISA kit, and the therapeutic effect of SCP on UC was clarified. Then, 16S rDNA sequencing was used to study the effect of SCP on the composition and diversity of gut microbiota. At the same time, GC-MS was used to determine the content of short chain fatty acids in intestinal contents. Finally, the relationship among gut microbiota, short chain fatty acids and inflammatory factors was analyzed, and to comprehensively explain the effect and mechanism of SCP on UC. Results: The results showed that SCP could significantly improve the physiological state of UC mice and regulate the level of inflammatory factors to normal levels. Meanwhile, SCP could significantly regulate the imbalance of gut microbiota and increase the content of SCFAs. In addition, the results of the correlation between gut microbiota and SCFAs showed that butyric acid, isobutyric acid and valeric acid had the highest correlation with gut microbiota. Conclusion: In conclusion, this research showed that SCP can inhibit inflammatory bowel disease by regulating the composition and metabolism of gut microbiota, and indicating that SCP may be used as adjuvant therapy for IBD patients.